ANALISIS NILAI KADAR ASPAL OPTIMUM DALAM PENGGUNAAN GETAH DAMAR (AGATHIS DAMMARA) SEBAGAI SUBSTITUSI TERHADAP CAMPURAN ASPAL AC-WC - Muhammad Nazib Tuhulele; Juliet G. Metekohy; S. G. M. Amaheka (JURNAL SIMETRIK, 2026)
The performance of Asphalt Concrete-Wearing Course (AC-WC) mixtures is influenced not only by mechanical strength but also by volumetric stability. The utilization of locally available natural materials as asphalt modifiers has attracted increasing attention due to sustainability considerations and the need to reduce dependence on petroleum-based resources. Damar resin (Agathis dammara), which is widely available in Indonesia and possesses adhesive and thermoplastic characteristics, has the potential to be used as a partial asphalt substitute. However, its influence on the volumetric performance of AC-WC mixtures remains insufficiently understood. This study aimed to evaluate the effect of 4% damar resin substitution on the Marshall characteristics of AC-WC mixtures and to determine the asphalt content range that satisfies the Marshall design criteria. An experimental approach based on the Marshall method was employed by testing asphalt contents ranging from 5.0% to 7.0%. The evaluated parameters included stability, flow, voids in mix (VIM), voids in mineral aggregate (VMA), and voids filled with bitumen (VFB) in accordance with the 2018 General Specifications for Road and Bridge Construction issued by the Directorate General of Highways (Bina Marga). The results indicate that conventional AC-WC mixtures satisfied all Marshall specification requirements within the asphalt content range of 6.0%–7.0%. The addition of 4% damar resin increased Marshall stability, with the highest stability value reaching 1344.01 kg. Nevertheless, deviations in VIM and VFB were observed at several asphalt contents, indicating an imbalance in the internal void structure of the mixture. These findings reveal that although damar resin can improve mechanical performance, it does not necessarily enhance the overall quality of AC-WC mixtures due to its adverse effects on volumetric stability. Therefore, volumetric parameters should be considered critical indicators in evaluating the feasibility and long-term performance of damar-modified asphalt mixtures.Keywords: AC-WC mixture; damar resin; Marshall characteristics; optimum asphalt content; volumetric stability.